Factors Associated with Acid Fast Bacilli and Sputum Culture Conversion in Patients with Multidrug-Resistant Tuberculosis in Surabaya - Naomi Rahmasena; Isnin Anang Marhana; Muhammad Yamin Sunaryo Suwandi; Tutik Kusmiati; Tuksin Jearanaiwitayakul (Biomolecular and Health Science Journal, 2021)
Introduction: Indonesia is a high incidence country of multidrug-resistant tuberculosis. There are approximately 11,000 MDR TB cases, 2.8% of them are new cases and 16% of them are relapse cases. Although guidelines for MDR-TB are frequently designed, medication freely provided, and centers for treatment duly expanded, studies on time to sputum culture conversion have been very limited in Indonesia. Therefore the aim of the study is to identify risk factors that effect on sputum and culture conversion.Methods: Data on short-term regimen for MDR TB in Dr. Soetomo General Hospital from January 1st – December 31st, 2018 were collected with a total sampling approach, and fulfill the inclusion and exclusion. Data were analyzed by computer software IBM SPSS Statistic 24 for windows. Results: Male is more likely to have delayed sputum conversion and culture conversion but no statistical difference is observed (p>0.05). Smoking history is more likely to have delayed sputum and culture conversion but only in sputum smear test shows a significant difference (p≤ 0.05). Alcohol consumption has delay effect on sputum and culture conversion but there is statistically difference in only culture conversion (p<0.05). The high baseline smear test also affects delay the sputum and culture conversion but only in sputum smear reveals a significant effect (p<0.05).Conclusion: In this present study, we identified sex, smoking history, high bacillary loads as significant factors on sputum conversion. In addition, we revealed that alcohol-consumption history is a significant factor affecting on culture conversion.